Low-cost farmer’s friendly technology can make the difference: A case study on Trichoderma sp. - N. SATHYANARAYANA, S.K. SAIN* and (Indian Phytopathology, 2016)
A case study was conducted to evaluate impact of low cost on-farm production technology for Trichoderma spp. being promoted by NIPHM since April 2013. Apart from 575 master trainers, 9130 farmers (including 3500 women) and 262 SHGs from various states of India have been trained. Over 1,50,000 growers got benefitted directly and indirectly. Application and use of T. harzianum demonstrated in 1680 ha tobacco fields during 2013-14 to 2015-16 in Andhra Pradesh and Karnataka showed 125 to 375 kg/ha increase in yield through reduced soil borne diseases and increased plant growth even after minimizing 3-4 chemicals pesticide sprays. Out of 1700 farmers, 300 have started production and use of Trichoderma sp. (> 1010 c.f.u./gm) within the cost Rs. 10-15/- per kg in Kerala and reportedly earned more profit. Technology is being promoted in ten districts of Meghalaya under RKVY project 2013-14 and in 150 villages (16 districts) of Tamil Nadu 2014-15.